Knowledge and Attitude Regarding Abortion among Undergraduate Health Science Students of Kathmandu Metropolitan City - Kumari Chaudhary, Archana; Bist, Amrit; Chaulagain, Rojina; Bhatta, Balkrishna; Kumar Chaudhary, Karan; Bhatta, Chetan (Clinical Medicine And Health Research Journal, 2023)
Background: The World Health Organization (WHO) defines abortion as pregnancy termination prior to twenty weeks of gestation or a fetus born weighing less than 500g. Abortion in Nepal was legalized in 2002, and the first legal abortion services started on March 18, 2004 (Safe Abortion Law). In developing regions, approximately 99% of the global maternal deaths in 2015 and early 8% of maternal deaths are abortion-related. Unsafe abortion is a public health concern because of its serious reproductive health consequences and impact on maternal morbidity and mortality. Methods: A descriptive cross-sectional study was conducted among 384 undergraduate students in colleges in Kathmandu Metropolitan City. Structured, self-administered questionnaires were used for data collection. Data were processed using IBS SPSS v. 25.0. Descriptive statistics and the chi-square test were used. Results: The study showed that two-thirds (66.7%) of study participants had good knowledge of abortion, while 33.3% had poor knowledge. Overall, there was a positive attitude toward abortion. Age, sex, residence, religion, ethnicity, type of family, educational level of parents, and occupation of parents were not significantly associated with levels of knowledge on abortion. Conclusion: Two-thirds of respondents had good knowledge of abortion. Still, a large proportion had poor knowledge regarding abortion, although the study participants were from a health science background. Therefore, it is strongly recommended that health education initiatives target such youth about abortion and its complications, which helps reduce morbidity and mortality associated with unsafe abortion.